-(4y+3z-4)=

Simple and best practice solution for -(4y+3z-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4y+3z-4)= equation:


Simplifying
-1(4y + 3z + -4) = 0

Reorder the terms:
-1(-4 + 4y + 3z) = 0
(-4 * -1 + 4y * -1 + 3z * -1) = 0
(4 + -4y + -3z) = 0

Solving
4 + -4y + -3z = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4y + -4 + -3z = 0 + -4

Reorder the terms:
4 + -4 + -4y + -3z = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -4y + -3z = 0 + -4
-4y + -3z = 0 + -4

Combine like terms: 0 + -4 = -4
-4y + -3z = -4

Add '3z' to each side of the equation.
-4y + -3z + 3z = -4 + 3z

Combine like terms: -3z + 3z = 0
-4y + 0 = -4 + 3z
-4y = -4 + 3z

Divide each side by '-4'.
y = 1 + -0.75z

Simplifying
y = 1 + -0.75z

See similar equations:

| x+1(2)+x(2)=14 | | 2x+8=8+2x | | 18=c+5/2 | | (x+2)(x-1)(x+1)=0 | | -5a+2a=12-15 | | 15-2(2w+1)=7w-2(7+w) | | -187=2-7(4x+7) | | 9l=3m | | 5(-5-3p)=-8p+3 | | 7t-(t-4)=25 | | (4a-4)(4a-1)=0 | | 0.7n+4.7=5.4n | | 5a+2a=12-15 | | -7(-3m-8)=98 | | 10-3(4x-2)=5x | | 4x-9=2x+1 | | 10x-7=5(x+1) | | 4x-29.2=7.5x-6.8 | | 3g-21=20+2g | | 5n=20(4+0.25) | | (X+2)(x^2-1)=0 | | 7685=345-5d | | -51z=-11.73 | | 2243+5754+789= | | 14*(3/2+x)=28 | | x^2+2r-360=0 | | 6x^2-22x-20=0 | | 14(3/2+x)=28 | | 6-0.25f=3 | | 6.4x=0.2816 | | -6t+17=3t-34 | | -23z+234=970 |

Equations solver categories